Efeitos das alterações no uso da terra sobre o regime hidrológico da bacia hidrográfica do rio Doce - Lyra, Bárbara Ucelis (2018)
The hydrological response due to changes in the soil use of watersheds can be evaluated through the construction of scenarios using hydrological models. However, most applications of hydrological simulations are performed in experimental basins and the changes in the soil use that are manifested on a large scale motivate the development of the hydrology of large basins. Thus, this study aimed to analyze the consequences of changes in land use in the hydrological behavior of the Doce river basin, which has a drainage area of approximately 86.715 km². The basin presents problems regarding water availability, floods, indiscriminate deforestation and inadequate soil management, mainly causing degradation of pastures. It was selected the Model of Large Basins (MGB-IPH), where daily data from 1990 to 2014, 11 fluviometric, 81 rainfall and 12 meteorological stations, numerical model of the land, soil maps, and use and land cover were used. The hydrological modeling was performed in the following steps: calibration of parameters (1990 and 2005), validation (2006 to 2014) and simulation of degraded pasture and deforestation scenarios (2000 to 2014). To evaluate the simulation´s adjustment, the visual analysis of the hydrograms (observed and simulated flows) and the values of the objective functions (ENS, ENSlog and Error Volume) were considered. In general, most stations presented adequate values, indicating a good flow adjustment. The degraded pastures causes average and maximum annual flows increasing and reduction in minimum annual flow. The correlation between the change in evapotranspiration and the percentage of degraded pasture showed a R² coefficient of 0,84, showing that the increase in the percentage of altered vegetation area also increases the impact on evapotranspiration. Was observed that the replacement of forests by pasture caused reductions in the average and minimum annual flows and increase in the maximum annual flow of the sub-basins analyzed. These results demonstrated the aggravations that these simulated scenarios can cause in the problems already found in the basin, such as floods and water shortages.